1984
DOI: 10.1002/ijc.2910330212
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR-antigen-associated restriction of EBV-specific cytotoxic T-cell colonies

Abstract: EBV-specific cytotoxic T cells can be generated in vitro in a secondary response. Several previous studies with bulk cultures provided evidence that cytotoxicity was restricted by HLA-A,B-related antigens. In the present family study, the EBV-specific cytotoxic T-cell response of a normal EBV-seropositive donor was analysed in detail by T-cell colony formation. Peripheral blood mononuclear cells were stimulated by the gamma-irradiated autologous lymphoblastoid cell line (LCL) and 3 days later seeded into agaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 22 publications
(7 reference statements)
4
49
1
Order By: Relevance
“…Both the FCS-and HS-grown autologous LCL were lysed equally well by the EBV-specilk CTL in keeping wiih previous findings thai virus-specific lysis is independent of scrum effects [19]. Second, the haploidentieal LCL target cells (donors 4,5,8) bearing the HLA-AI, -B8, -DR3 paternal haplotype were not lysed by the specific CTL (Fig. !b. c) even though this haplolype was expressed by the autologous LCL used in the initial stimulation.…”
Section: Cytotoxieity Asiayssupporting
confidence: 86%
“…Both the FCS-and HS-grown autologous LCL were lysed equally well by the EBV-specilk CTL in keeping wiih previous findings thai virus-specific lysis is independent of scrum effects [19]. Second, the haploidentieal LCL target cells (donors 4,5,8) bearing the HLA-AI, -B8, -DR3 paternal haplotype were not lysed by the specific CTL (Fig. !b. c) even though this haplolype was expressed by the autologous LCL used in the initial stimulation.…”
Section: Cytotoxieity Asiayssupporting
confidence: 86%
“…A review of earlier literature shows that CD4 ϩ T cells capable of recognizing autologous LCL cells have been detected in various in vitro settings, usually after LCL stimulation, where the effector cells were derived from either fetal cord blood, 36,37 EBVseronegative donors, 35,38 EBV-seropositive donors, [39][40][41][42][43] or, most recently, patients with infectious mononucleosis undergoing primary EBV infection. 21 In some cases, further analysis at the clonal level showed these cells to be HLA II restricted or to recognize LCL cells but not mitogen-activated lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…21 In some cases, further analysis at the clonal level showed these cells to be HLA II restricted or to recognize LCL cells but not mitogen-activated lymphoblasts. 21,38,[40][41][42] However, most of these studies did not look for reactivity against individual EBV antigens and so never showed EBV specificity. We suggest that many of these responses were, as described here, LCL specific.…”
Section: Discussionmentioning
confidence: 99%
“…Rosetted T cells were also maintained as polyclonal CTL lines by restimulation with recombinant interleukin-2 (rlL-2) and specific irradiated transformants. T cell clones and PHA blasts were generated as previously described (Misko et al, 1984;Burrows et al, 1990a).…”
mentioning
confidence: 99%
“…Polyclonal CTLs from donor IM and T cell clones from donor LC were tested for cytotoxicity in standard 5 h SlCr-release assays (Misko et al, 1984). The target panel included the type A and type B autologous LCLs and autologous PHA blasts.…”
mentioning
confidence: 99%